PEMUTUSAN HUBUNGAN KERJA KARENA KESALAHAN BERAT - Sofa Laela (The Juris, 2020)
Issues regarding the rights of the workers who serve them are one of the main concerns of the government and the law. Manpower issues are a problem for every Indonesian citizen because everyone has the right to a decent job and welfare. Termination of employment carried out by employers against workers / laborers due to serious mistakes, workers/laborers will carry out dispute resolution through non-litigation and litigation to obtain their rights as a result of termination of employment. Issues regarding the rights of the workers who serve them are one of the main concerns of the government and the law. Manpower issues are a problem for every Indonesian citizen because everyone has the right to a decent job and welfare. The mistake is What is the positive law that establishes employment relationships because of serious mistakes? The method used is normative juridical. The data used are primary data and secondary data. In an effort to answer or solve the problems raised in this study, qualitative data analysis methods are used. Analysis: Judges in legal considerations issue a decision regarding th.e worker / laborer on the grounds of serious error namely in accordance with the provisions of Article 156 Law Number 13 Year 2003 Regarding Manpower, the plaintiff does not want to work again so it is entitled for severance pay, long service pay, compensation pay for entitlements, linked to Article 156 Law Number 13 Year 2003 and its legal implications arises with the issuance of a decision regarding termination of employment against workers / laborers due to serious mistakes, namely: Termination of employment must pay compensation in accordance with Article 156 Law Number 13 of 2003 concerning Manpower the plaintiff gets his rights consisting of severance pay, long service pay, money replacement.